Model building operation flows - O. V. Demidenko; V. A. Kazakov; S. M. Kuznetsov; A. E. Alekseev (Вестник СибАДИ, 2017)
In this article, building traffic management issues presented by a formal modeling methods. The features of the main structural element of the construction of the production system - a specialized stream. And revealed the necessity of joint planning and delivery volumes of consumption of building material resources. On the basis of the study authors developed a discrete time-probabilistic model of the interaction of building streams and transport process. The proposed recommendations for the design of transport and technological maintenance of building streams by material resources will ensure the continuity and regularity of production activities and consumption of materials, enhance organizational level of building production.